Determinants of Financial Distress in Food and Beverage Companies Listed on the Indonesian Stock Exchange - Ayu Lestari; Ika Yustina Rahmawati (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The research investigates the impact of financial ratios and macroeconomic factors on financial distress. Financial ratios are measured by profitability (ROA), liquidity (CR), and leverage (DER). Macroeconomic factors are measured by inflation and interest rates. This analysis uses secondary data from 71 food and beverage companies listed on the Indonesia Stock Exchange for the period 2021–2024, yielding 124 observations tested using descriptive statistics, panel logistic regression, odds ratios, and classification accuracy. Financial distress is measured in terms of the Altman Z-score, followed by hypothesis testing with Stata 17. Findings show a negative effect of profitability and interest rates on financial distress, and a positive effect of leverage. Furthermore, liquidity and inflation are not affecting financial distress. In this study, the novelty comes from utilizing macroeconomic factors as independent variables, thereby provides new insights into the roles of macroeconomics on financial distress.